If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(x-18)-8(x+15)=27-9(x-3)
We move all terms to the left:
2(x-18)-8(x+15)-(27-9(x-3))=0
We multiply parentheses
2x-8x-(27-9(x-3))-36-120=0
We calculate terms in parentheses: -(27-9(x-3)), so:We add all the numbers together, and all the variables
27-9(x-3)
determiningTheFunctionDomain -9(x-3)+27
We multiply parentheses
-9x+27+27
We add all the numbers together, and all the variables
-9x+54
Back to the equation:
-(-9x+54)
-6x-(-9x+54)-156=0
We get rid of parentheses
-6x+9x-54-156=0
We add all the numbers together, and all the variables
3x-210=0
We move all terms containing x to the left, all other terms to the right
3x=210
x=210/3
x=70
| 5x+7=21-9x | | t+11=3 | | n8=82 | | 7+y/4=35 | | 4c-20=3c-15 | | |2a+5|=|a+6| | | 10x3+10x=13x-3+7x | | 3/m+2=-21 | | 10x+3x+5=109 | | 107=-7m+6(-3m-3) | | j-j+j+4j+4j=9 | | 0.9(w+-20)=-7.2 | | 5=-7a+8+4 | | t-11=13 | | 6t=96 | | 4n-2=44 | | 14-8m=-13-5m | | |3x+5|+10=7 | | -5-9x=3-(2-3x)-8 | | 2y+0.9=-1.04 | | 8(2x-5)-4x=-10+7x | | 4(b-65)=76 | | -342=-9x | | -x+3=4x-17/ | | 4x-8=10x-2 | | −4x+3=23. | | 1=3n | | 2(m-4)=8+2m | | a-1.7=-4.9 | | 23x-3=17 | | 2p-10=32 | | 4(4x-7)-5=16x-33 |